Development of adsorptive hybrid filters to enable two-step purification of biologics. Issue 2 (17th February 2017) - Singh, Nripen; Arunkumar, Abhiram; Peck, Michael; Voloshin, Alexei M.; Moreno, Angela M.; Tan, Zhijun; Hester, Jonathan; Borys, Michael C.; Li, Zheng Jian
ABSTRACT: Recent progress in mammalian cell culture process has resulted in significantly increased product titers, but also a substantial increase in process- and product-related impurities. Due to the diverse physicochemical properties of these impurities, there is constant need for new technologies that offer higher productivity and improved economics without sacrificing the process robustness required to meet final drug substance specifications. Here, we examined the use of new synthetic adsorptive hybrid filters (AHF) modified with the high binding capacity of quaternary amine (Emphaze™ AEX) and salt-tolerant biomimetic (Emphaze™ ST-AEX) ligands for clearance of process-related impurities like host cell protein (HCP), residual DNA, and virus. The potential to remove soluble aggregates was also examined. Our aim was to develop a mechanistic understanding of the interactions governing adsorptive removal of impurities during filtration by evaluating the effect of various filter types, feed streams, and process conditions on impurity removal. The ionic capacity of these filters was measured and correlated with their ability to remove impurities for multiple molecules. The ionic capacity of AHF significantly exceeded that of traditional adsorptive depth filters (ADF) by 40% for the Emphaze™ AEX and by 700% for the Emphaze™ ST-AEX, providing substantially higher reduction of soluble anionic impurities, including DNA, HCPs and model virus. Nevertheless, we determined that ADF with filter aid provided additional hydrophobic functionality that resulted in removal of higher molecular weight species than AHF. Implementing AHF demonstrated improved process-related impurity removal and viral clearance after Protein A chromatography and enabled a two-step purification process. The consequences of enhanced process performance are far reaching because it allows the downstream polishing train to be restructured and simplified, and chromatographic purity standards to be met with a reduced number of chromatographic steps.